2001
DOI: 10.1042/bj3590721
|View full text |Cite
|
Sign up to set email alerts
|

The shorter zinc finger protein ZNF230 gene message is transcribed in fertile male testes and may be related to human spermatogenesis

Abstract: The zinc finger gene family represents one of the largest in the mammalian genome, with several of these genes reported to be involved in spermatogenesis. A newly discovered gene has been identified that is expressed abundantly in the testicular tissue of fertile men as determined by mRNA differential display. The gene encodes a C3HC4-type zinc finger protein motif (ring finger motif) consistent with a role in pre-meiotic or post-meiotic sperm development. The gene was named ZNF230 and mapped to the short arm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Zinc finger protein is one kind of transcription factor, which is widely existed in organisms, and plays an important role in cell proliferation, cell differentiation and cell apoptosis (9)(10)(11)(12). At present, several studies demonstrated that zinc finger protein was expressed specifically in testis, such as ZNF230 (13), ZNF105 (14) and ZNF300 (15), and closely associated with spermatogenesis and male reproduction. ZNF185, also known as ZFP185, is belonging to the ZNF family and identified by Heiss for the first time in 1997 (16).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc finger protein is one kind of transcription factor, which is widely existed in organisms, and plays an important role in cell proliferation, cell differentiation and cell apoptosis (9)(10)(11)(12). At present, several studies demonstrated that zinc finger protein was expressed specifically in testis, such as ZNF230 (13), ZNF105 (14) and ZNF300 (15), and closely associated with spermatogenesis and male reproduction. ZNF185, also known as ZFP185, is belonging to the ZNF family and identified by Heiss for the first time in 1997 (16).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc finger proteins (ZNFs) consist of a series of molecules that have important biological functions . Recently, several studies have reported different zinc finger proteins, including ZNF185, ZNF230, ZNF105, and ZNF300, as being involved in spermatogenesis and male reproduction . Notably, ZNF185 belongs to the ZNF family and was identified by Heiss in 1997.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Recently, several studies have reported different zinc finger proteins, including ZNF185, ZNF230, ZNF105, and ZNF300, as being involved in spermatogenesis and male reproduction. [8][9][10][11] Notably, ZNF185 belongs to the ZNF family and was identified by Heiss in 1997. It is located on the DXS52 region of Shutong Fan and Yuhan Zhao are co-first authors.…”
mentioning
confidence: 99%
“…There is growing interest to extend this method to various RING fingers; therefore, we felt the need to elucidate their atomic structures to identify appropriate positions for the grafting of active sites. Human RING finger protein 141 (RFP141) consists of 230 amino acids and is considered to serve as a germ cellā€specific transcription factor during spermatogenesis . The Simple Modular Architecture Research Tool (SMART) database predicted the Cā€terminal zinc finger of RFP141 (RFP141C) as a RING finger.…”
Section: Introductionmentioning
confidence: 99%